+0  
 
0
56
1
avatar

How do you get from ( |z| )^2 = a^2 + b^2 to -2z = -2a + 2i - b

Guest Sep 14, 2018
 #1
avatar+93905 
+2

How do you get from ( |z| )^2 = a^2 + b^2 to -2z = -2a + 2i *- b

 

You missed the times sign.

 

\(z=a+bi\\ \text{|z| is the distance of point Z from the origin.}\\ \text{Using pythagorases theorem we get }|z|^2=a^2+b^2\\ \\~\\ Since z=a+bi\\ -2z=-2(a+bi)\\ -2z=-2a-2bi\)

Melody  Sep 15, 2018

7 Online Users

avatar

New Privacy Policy

We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive information about your use of our website.
For more information: our cookie policy and privacy policy.